Педагогічна діяльність професора Юрія Полянського в Академічній гімназії Львова - Томенюк, О. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
Period of work of professor Jury Polianskyi in Academic gymnasium in L’viv includes long interim of time (1920–1937). History of development of Academic gymnasium in L’viv and general results of scholar’s pedagogic activity in this scientific center are represented at this article. One of new aspects, which were not published before, is a collection of reviews, dedicated to Polianskyi, written by his former students. Geography textbook “Pozaevropeis’ki krai ta moria”, published by this scientist in 1938, is analyzed.